Influence of household cleaning practices on the magnitude and variability of urinary monochlorinated bisphenol A - Andra, Syam S.; Karaolis, Constantinos; Makris, Konstantinos C.; Charisiadis, Pantelis; Kalyvas, Harris (My University, 2014)
Low-dose health effects of BPA have not been adequately explored in the presence of BPA metabolites of chlorinated structure that may exert larger estrogenic effects than those of their parent compound. We hypothesized that chlorine-containing cleaning products used in household cleaning activities could modify the magnitude of total urinary BPA concentration measurements via the production of chlorinated BPA (ClBPA) derivatives. Our objective was to investigate the influence of typical household cleaning activities (dishwashing, toilet cleaning, mopping, laundry, etc.) on the magnitude and variability of urinary total BPA and mono-ClBPA levels in the general adult population. A cross-sectional study (n = 224) included an adult (≥ 18 years) pool of participants from the general population of Nicosia, Cyprus. First morning urine voids were collected, and administered questionnaires included items about household cleaning habits, demographics, drinking water consumption rates and water source/usage patterns. Urinary concentrations of total BPA (range: 0.2–82 μg L− 1), mono-ClBPA (16–340 ng L− 1), and total trihalomethanes (0.1–5.0 μg L− 1) were measured using gas chromatography coupled with triple quadrupole mass spectrometry and large volume injection. Linear multiple regression analysis revealed that dishwashing along with age and gender (females) were able to predict urinary mono-ClBPA levels (ng g− 1), even after adjusting for covariates; this was not the case for urinary total BPA levels (ng g− 1). Significant (p < 0.001) association was observed between urinary mono-ClBPA and THM levels, underlying the important role of disinfectant (chlorine) in promoting formation of both ClBPA and THM. Urinary mono-ClBPA levels were measured for the first time using an appreciable sample size, highlighting the co-occurring patterns of both total BPA and mono-ClBPA. Epidemiological studies and probabilistic BPA risk assessment exercises should consider assessing daily intake estimates for chlorinated BPA compounds, as well.
Keywords: Bisphenol A; Chlorinated BPA; Trihalomethanes; Drinking water; Biomarkers of exposure; Disinfection